Effectiveness Of Health Promotion In Improving Clean And Healthy Living Behavior (PHBS) In The Community - Rahmat Pannyiwi; Riski Muhammad Akbar Kaharuddin (International Journal of Health Sciences, 2026)
ABSTRACT Health promotion is a crucial effort to improve public health through changes in healthy lifestyle behaviors. Clean and Healthy Living Behavior (PHBS) is a crucial indicator in creating a healthy and productive society. This study aims to determine the effectiveness of health promotion in improving PHBS in the community. This research uses a quantitative approach with a pre-experimental design through the one-way method. group pretest-posttest The research sample consisted of 40 respondents selected using purposive sampling techniques . Data were collected using a questionnaire regarding PHBS knowledge and behavior before and after health promotion. Data analysis was performed using a Paired T- test . The results of the study showed an increase in the average PHBS score of the community after health promotion. The average score before the intervention was 58.40, increasing to 82.15 after the intervention. The statistical test results showed a p value of 0.000 (p < 0.05), indicating a significant effect of health promotion on improving PHBS in the community. It was concluded that health promotion is effective in increasing clean and healthy living behaviors in the community. Therefore, health promotion activities need to be carried out continuously to increase public awareness and healthy behaviors. Keywords: Health Promotion, PHBS , Healthy Behavior, Community, Health Education